Processus de qualification et construction d’un compromis institutionnel territorialisé. La gestion intégrée de l’eau par bassin dans le canton de Fribourg (Suisse) - Arnaud Buchs (Développement Durable et Territoires)
This article aims at understanding the qualification of natural resources as an endogenous and iterative normative process involving actors with different interests, often conflicting. Promoted by the Swiss federal authorities since the early 2000s, integrated watershed management is considered an imperative for sustainable water use. We consider the case of the renewal process of the water law in the Canton of Fribourg (Switzerland) aiming at implementing an integrated watershed management. However, its operationalization leads us to question the gap vis-à-vis the theoretical model. Thanks to a socio-economics approach, we strive to overpass the “naturalized” and “functionalist” visions of watershed management. In this reserach, qualification is considered as a process that shapes resources attributes, but also the modes of coordination and the regulation scale recommended. This analysis reveals that integrated watershed management has to be considered as a territorial institutional compromise: first, the extent of sectoral integration is not given (which uses are regulated and how?); secondly, the scale finally adopted does not fit exactly the watershed, even though it is presented as the perfect functional space for regulating water use.